Diseño e implementación de un Sistema de Control de Costos - Devandas-Chavarría, Octavio (Instituto Tecnológico de Costa Rica, 2007)
The object of this project was to develop a system to keep control of the expenses made by the company in each project. In order to achieve these objective several sheets of Microsoft Excel were programmed. As a result, the program created has the capability to structure the project in activities in this way it is possible to keep track of every one of them individually; the program compares the budget with the actual expenses in each activity, it do this weekly and in a accumulative way, it realize a projection of the final cost of the project; it also tells the users whether the project is on schedule or not; it makes an interpretation of the data based on factors calculated according to the actual situation of the project; the information can be resumed which facilitates the creation of reports that can be given to the clients or management, it also counts with accounting worksheets that help to keep track of the amount of money that has to be collected, to be paid, or that is pending to be collected. Of the results the conclusion is that the project developed fulfills the objectives stated, and it also counts with administrative tools, that help with the administration of any given project, taking into account important factors in the area such as cost, quality, security and time.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2007.
Keywords: Hoja de cálculo; Modelos de control; Eficiencia; Presupuesto; Guías de uso